HUBUNGAN JUMLAH CURAHAN AIR DARI SISTEM IRIGASI BOOM DENGAN MUNCULNYA GEJALA AWAL PENYAKIT HAWAR DAUN BAKTERI DI PEMBIBITAN TANAMAN AKASIA (Acacia crassicarpa Cunn Ex Benth) - Uci Oktavia; Yetti Elfina; Defri Yoza (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to determine the relationship of the amount of water flow from the boom irrigation system with an attack of bacterial leaf blight in seedlings A. crassicarpa. This research has been conducted in Kerinci Central Nursery (KCN) Plant Nursery Acacia PT Riau Andalan Pulp and Paper (RAPP) in the District of Pangkalan Kerinci, Pelalawan Riau from September to November 2014. The study was conducted experimentally using correlation method to determine the relationship of the amount of water flow irrigation systems boom (x) with an attack of bacterial leaf blight (y). The research was done by measuring the amount of water flow from irrigation boom during watering. Data were statistically analyzed by simple linear regression analysis. The results showed that the relationship the amount of water flow from the irrigation system is positively correlated boom of 36.8% (increases linearly and have not yet reached the optimum point) to the emergence of the first symptoms of bacterial leaf  Keywords: A. crassicarpa, the amount of irrigation water flow and bacterial leaf blight boom